MEDIA SOSIAL SEBAGAI SARANA MEMBANGUN KERUKUNAN PADA KOMUNITAS YOUNG INTERFAITH PEACEMAKER (YIPC) - M Thoriqul Huda; Okta Filla Filla (UIN Sunan Kalijaga Yogyakarta, 2019)
Diversity is a reality for the Indonesian nation, one form of diversity, namely religion. Religion is a guide from the creator of how humans can live in differences so as to create an orderly and harmonious life. However, the phenomenon that occurs is just the opposite where religion in fact makes someone to claim the truth of each religion. This certainly becomes a serious conflict for the Indonesian people considering that Indonesia is a plural country and should have an understanding of tolerance. Actually tolerance is not just a concept that must be understood but must be realized in attitudes and behaviors so that a harmony between religious people will be realized. Amid the current global developments, technological sophistication cannot be dammed so that people can easily receive information. Responding to this phenomenon if we especially as youths who basically have an important role in building inter-religious harmony cannot properly take advantage of the existence of social media, it will easily accept and even spread hoax issues, the impact of this will certainly damage the relationship between harmony religious people should be as young people as filtering and wise in the use of social media. Through social media, we as young people can do positive things as well, pour creative ideas to channel talents that we have such as making writings or images so that they can be enjoyed by others, communicating with distant friends or adding friends by joining a social group that later will add insight and foster harmony among others Keywords: Social Media, Harmony, YIPC